(untitled) (Journal of Parents and Teachers, 2019)
The tutorial action requires a specific work with its own time. From its action, it will be possible to mainstream didactic resources (methodology, materials, organizational means) to enrich the teaching / learning action. The work that tutors and tutors deploy must come to shape experiences of capacity building, skills and content that allow self-esteem, balance, decision-making and cooperation to work, providing suggestions for integrating convergent actions of the family and the rest of professors and teachers who intervene with the group.